Transdermal material construction in covid 19 vaccine delivery: a microneedle approach - Chowdhury, Tasnia Farheen (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.